Etika Pengambilan Keuntungan Dalam Transaksi Jual Beli Perspektif Mazhab Syafi’i Dan Jumhur Ulama - Zaenol Hasan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2021)
One of the supports in the country's economy is market health, both the goods and services market, the money market, as well as the labor market. Market health depends on market mechanisms that are able to create a balanced price level, namely the price level generated by the interaction between healthy supply and demand forces. If this condition is reasonable and normal without any violations, such as hoarding (ikhtikar), the price will be stable. This type of research is library research. The result showed that the Shafi’I Mazhab emphasized the prohibition of tas’ir (price fixing) by the government because it would cause injustice to one of the parties in the market, while according to the majority of scholars tas’ir (price fixing) by the government is permitted and even obligatory on the ground of maslahat, namely to avoid hoarding (ihtikar), monopoly, and fraud commited by traders.